Свидание по заданию: [роман] / Галина Куликова - Куликова Галина Михайловна (Галина Куликова, 2016)
Экземпляры: ф.17 (20160608) / Инвентарный номер: 51751 / Цена: 226.00 / Авт.знак: К 90 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6